Reasons for non-disclosure of HIV-Positive status to healthcare providers: a mixed methods study in Mozambique - Laura Fuente-Soro; Antía Figueroa-Romero; Sheila Fernández-Luis; Orvalho Augusto; Elisa López-Varela; Edson Bernardo; Anna Saura-Lázaro; Paula Vaz; Stanley C. Wei; Peter R. Kerndt; Tacilta Nhampossa; Denise Naniche (BMC, 2023)
Abstract Background Non-disclosure of known HIV status by people living with HIV but undergoing HIV testing leads to waste of HIV testing resources and distortion of estimates of HIV indicators. In Mozambique, an estimated one-third of persons who tested positive already knew their HIV-positive status. To our knowledge, this study is the first to assess the factors that prevent people living with HIV (PLHIV) from disclosing their HIV-positive status to healthcare providers during a provider-initiated counseling and testing (PICT) campaign. Methods This analysis was nested in a larger PICT cross-sectional study performed in the Manhiça District, Southern Mozambique from January to July 2019, in which healthcare providers actively asked patients about their HIV-status. Patients who tested positive for HIV were crosschecked with the hospital database to identify those who had previously tested positive and were currently or previously enrolled in care. PLHIV who did not disclose their HIV-positive status were invited to participate and provide consent, and were interviewed using a questionnaire designed to explore barriers, patterns of community/family disclosure, and stigma and discrimination. Results We found that 16.1% of participants who tested positive during a PICT session already knew their HIV-positive status but did not disclose it to the healthcare provider. All the participants reported previous mistreatment by general healthcare providers as a reason for nondisclosure during PICT. Other reasons included the desire to know if they were cured (33.3%) or to re-engage in care (23.5%). Among respondents, 83.9% reported having disclosed their HIV-status within their close community, 48.1% reported being victims of verbal or physical discrimination following their HIV diagnosis, and 46.7% reported that their HIV status affected their daily activities. Conclusion Previous mistreatment by healthcare workers was the main barrier to disclosing HIV-positive status. The high proportion of those disclosing their HIV status to their community but not to healthcare providers suggests that challenges with patient-provider relationships affect this care behavior rather than social stigma and discrimination. Improving patient-provider relationships could increase trust in healthcare providers, reduce non-disclosures, and help optimize resources and provide accurate estimates of the UNAIDS first 95 goal.